PENINGKATAN HASIL BELAJAR EKONOMI DAN SUMBER DAYA MELALUI PENGEMBANGAN DESAIN PEMBELAJARAN - Arita Marini (Perspektif Ilmu Pendidikan, 2010)
This classroom action research aims at improvingthe students’ learning achievement in Economics and Resources by developing learning design. In this research Kemmis and Taggart model was employed in three cycles. The population of this research covered the students of Elementary School Teacher Education Department in State University of Jakarta. The samples were selected by simple random sampling at amount of 30 students. Instrument used in this research was test in learning achievement of Economics and Resources.The data were analyzed by counting the mean of each cycle. The result of study showed that there is improvement of learning achievement in each cycle. The means of cycle 1, 2, and 3 are 65, 72, and 80 respectively. In the third cycle, the learning achievement of the students has reached the determine indicators. Based on research findings, it can be concluded that the learning of achievement in Economics and Resources can be improved by improving learning design.